Mortality After Magnetic Resonance Imaging of the Brain in Patients With Cardiovascular Implantable Devices. (January 2018) - Padmanabhan, Deepak; Jondal, Mary L.; Hodge, David O.; Mehta, Ramila A.; Acker, Nancy G.; Dalzell, Connie M.; Kapa, Suraj; Asirvatham, Samuel J.; Cha, Yong-Mei; Felmlee, Joel P.; Watson, Robert E.; Friedman, Paul A.
Abstract : Background: Use of magnetic resonance imaging (MRI) brain is restricted in patients with cardiovascular implantable electronic devices (CIEDs). We proposed to determine whether mortality difference exists for patients with non–MRI-conditional CIEDs undergoing brain MRI compared with controls. Methods and Results: Retrospective analysis of prospectively collected data was performed to compare all-cause mortality in patients with CIEDs undergoing brain MRI (CIED-MRI) with 3 control groups matched for age, sex, imaging year, and type of CIED: (1) no CIED, brain MRI (no–CIED-MRI); (2) CIED, brain computerized tomography (CT) scan (CIED-CT); and (3) no CIED, brain CT (no–CIED-CT). The primary outcome was a significant difference ( P <0.05) between estimated mortality rates. Secondary outcomes were changes in device function before and after brain MRI. The estimated all-cause mortality at 5 years for the CIED-MRI group [mean age (±SD), 68.2 years (15.3 years); 61.2% men] was not significantly different from patients who underwent CT with or without a device (CIED-CT group: hazard ratio, 0.814; 95% confidence interval, 0.593–1.117; P =0.2; no–CIED-CT group: hazard ratio, 1.149; 95% confidence interval, 0.818–1.613; P =0.4). There was a significant increase in mortality between CIED-MRI and no–CIED-MRI groups (hazard ratio, 1.463; 95% confidence interval, 1.019–2.099; P =0.04). Conclusions: Brain MRI in patients with CIEDs does not carry an increased mortality risk compared with brain CT and can be performed with adherence to appropriate procedural protocols. Abstract : Supplemental Digital Content is available in the text.